Contribuições para o Chaco como Bioma no Brasil - PEDRO HENRIQUE BARRERA DE MOURA GOMES (2021)
Chaco is a biome that involves Argentina, Paraguay, Bolivia, and a small fragment in Brazil. 40% of their original size was deforested. This study aims to identify bibliometrics trend in Chaco studies. We used the Bibliometrix package of Software R. Studies regarding deforestation in Chaco are poorly developed, with only 202 papers and annual growth of 5% since 1998. Although few publications, research on Chaco has high impact on the H-index and a high concentration of articles produced by few authors. “Deforestation” proved to be the key word with the greatest number of appearances and the greatest number of interactions between keywords, that is, this theme proves to be one of the most relevant to the focus of research on events in Chaco. The 2011-2012 presented the highest peak of production growth, highlighting two articles that contributed most. Currently shows growth potential especially for related research land use and cover, population dynamics, and defragmentation. Argentina has the largest number of publications and behaves as the center of the networking of cooperation, which makes this country ideal for partnerships in this field. For the second chapter, we verified vegetation changes according to the altimetric profile, whose elevation profile at 70km distance from Porto Murtinho marked the difference between the physiognomies. There was also a difference in soils between the study areas, among which the area close to Porto Murtinho has as primary characteristic yellow and gray soils, with slow and saline drainage. An investigation of these soils would provide more information to understand how and what soil conditions support Chaco formations. The Chaco fragments next to the highway and on the side roads have undergone anthropic interference, and, therefore, this disturbance must be taken into consideration for future proposals for studies of conservation and management of this biome studied so incipiently. It is noticeable that the altitude controls Chaco's progress as the elevation increases, as it can also be related to the difference in temperature, climate, and different soils along the highway. The Chaco de Porto Murtinho formations are degraded and fragmented. This fragmentation exposes the vulnerability of these small formations to invasion by exotic species and native species that are better adaptable. Therefore, it is essential to encourage more intensive research, conservation, and management actions in the Chaco region, especially by introducing the Bio-oceanic Corridor, constructing a highway that will connect Brazil, Paraguay, and Chile, being a new source of anthropic pressure.